Bacterial adhesion to worn silicone hydrogel contact lenses - Santos, Lívia (2008)
Purpose. The aim of this study was to, firstly, investigate whether silicone-hydrogel contact lenses (CL) are more or less susceptible to bacterial adhesion than conventional ones and, secondly, assess the influence of lens wear in the extent of bacterial adhesion. Four silicone-hydrogel CL (galyfilcon A, balafilcon A, lotrafilcon A, and lotrafilcon B) and one conventional hydrogel (etafilcon A) CL were tested. Methods. Bacterial adhesion experiments were performed on unworn and worn CL using the strain Staphylococcus epidermidis 9142. Worn lenses were obtained from a group of 31 subjects fitted with a silicone-hydrogel CL in one eye and a conventional hydrogel CL as contralateral pair. These lenses were used on a daily basis in combination with a multipurpose lens care solution. Adhesion assays were carried out in a parallel plate flow chamber, followed by image analysis. Hydrophobicity, roughness, and topography of the lenses surfaces were assessed through contact angle measurements and atomic force microscopy. Results. Unworn conventional and silicone-hydrogel CL were equally susceptible to bacterial adhesion of S. epidermidis. Conversely, worn conventional hydrogel (etafilcon A) were more prone to bacterial adhesion than worn silicone-hydrogel materials, which exhibited similar adhesion extents among them. The results also showed that the lens surface properties such as hydrophobicity, roughness, and surface topography changed during wear. The alteration of surface hydrophobicity of silicone and conventional hydrogel CL during wear had a great impact on lens bacterial adhesion susceptibility. Accordingly, balafilcon A becomes significantly less hydrophobic and less prone to bacterial adhesion after lens wear, whereas etafilcon A becomes more hydrophobic and also more susceptible to bacterial adhesion (p < 0.05). Conclusions. Worn silicone-hydrogel galyfilcon A, balafilcon A, lotrafilcon A, and lotrafilcon B are equally prone to microbial adhesion of S. epidermidis and generally less susceptible than the conventional hydrogel.